Pengaruh Lingkungan Sosial Terhadap Perilaku Agresivitas Remaja di Lingkungan Tambaklorok Semarang - Iqlima Dian Handayani (Jurnal Maritim Polimarin, 2018)
Today, the lives of our teenagers are susceptible to aggressive behavior, for example throwing harsh words such as berating, insulting, fighting each other, hitting, fighting, brawls to murder for a small problem. The research aim is want to know whether there was any influence of the social environment on the aggressive behavior of adolescents. The type of research used in this study is explanatory research. Data collection method was observation and interviews. Analysis of the data used is product moment correlation analysis to test the social environment relationship to social behavior. Product moment correlation analysis show that: respondents regarding the quality of the social environment are included in good category, with an average rating of 5.21; respondents regarding the quality of adolescent's aggressive behavior are included in low category with an average value of 5.38; and while regression analysis for social environment variables are +0.718.